2019
DOI: 10.1039/c8fd00217g
|View full text |Cite
|
Sign up to set email alerts
|

Photodetachment and photoreactions of substituted naphthalene anions in a tandem ion mobility spectrometer

Abstract: Substituted naphthalene anions (deprotonated 2-naphthol and 6-hydroxy-2-naphthoic acid) are spectroscopically probed in a tandem drift tube ion mobility spectrometer (IMS). Target anions are selected according to their drift speed through nitrogen buffer gas in the first IMS stage before being exposed to a pulse of tunable light that induces either photodissociation or electron photodetachment, which is conveniently monitored by scavenging the detached electrons with trace SF 6 in the buffer gas. The photodeta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…2b), which was assigned to the principal Franck-Condon active mode for excitation of the S 1 (pp*) state (calculated n 32 (a 0 ) = 437 cm À1 ) through Franck-Condon-Herzberg-Teller simulations. 21 It is also worth noting that this vibrational structure is consistent with the principal Franck-Condon modes for direct photodetachment characterised by an earlier cryogenic photoelectron spectroscopy experiment, 22 involving n 32 (a 0 ) = 422 cm À1 (neutral), which is an in-plane CCC bending mode and has most displacement localised on the oxygen-containing benzyl ring. In the present photoelectron spectra, the vibrational structure over the prompt detachment band in the photoelectron spectra is presumably associated with prompt autodetachment through electron shake-off by the n 32 mode of the anion excited state.…”
Section: Frequency-and Angle-resolved Photoelectron Imagingsupporting
confidence: 81%
See 4 more Smart Citations
“…2b), which was assigned to the principal Franck-Condon active mode for excitation of the S 1 (pp*) state (calculated n 32 (a 0 ) = 437 cm À1 ) through Franck-Condon-Herzberg-Teller simulations. 21 It is also worth noting that this vibrational structure is consistent with the principal Franck-Condon modes for direct photodetachment characterised by an earlier cryogenic photoelectron spectroscopy experiment, 22 involving n 32 (a 0 ) = 422 cm À1 (neutral), which is an in-plane CCC bending mode and has most displacement localised on the oxygen-containing benzyl ring. In the present photoelectron spectra, the vibrational structure over the prompt detachment band in the photoelectron spectra is presumably associated with prompt autodetachment through electron shake-off by the n 32 mode of the anion excited state.…”
Section: Frequency-and Angle-resolved Photoelectron Imagingsupporting
confidence: 81%
“…Other experiments which subjected PAHs to interstellar conditions found extensive hydrogenation, oxygenation, and hydroxylation, ultimately leading to more complex organics. 20 In a recent contribution, one of the present authors reported a photodetachment study on 2-Np À thermalised to T E 300 K, 21 providing an action spectrum of the S 1 (pp*) band as well as identifying several other weak spectral features spanning the electron detachment threshold, which were attributed to a progression of dipole-bound states. Two recent investigations using cryogenic photoelectron and photodetachment techniques have reported near-threshold spectra of 2-Np À , and also identified dipole-bound states.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations